THE INFLUENCE OF FINANCIAL MANAGEMENT ON BUSINESS GROWTH IN MEDIUM-SCALE TITLE COMPANIES - Muhammad Teguh Setiadi; Fahmi Amirulloh Anwar; Ahmad Solihin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study aims to analyze the influence of financial management on business growth in medium-sized companies thru a literature review approach. Financial management is seen as a key factor in maintaining the stability, efficiency, and operational sustainability of a company, particularly in the face of challenges related to capital limitations and market dynamics. The research method used is a Systematic Literature Review (SLR) with a descriptive-analytic approach to various previous research results published between 2015 and 2025. Data was collected from various scientific sources such as Scopus, ScienceDirect, Emerald, Google Scholar, and DOAJ, focusing on the themes of "financial management," "business growth," and "medium enterprises." The study results indicate that effective financial management practices, including cash management, investment decisions, and optimal capital structure, have a positive relationship with increased productivity and competitiveness of medium-sized companies. Additionally, the implementation of financial digitalization thru technologies like fintech and cloud accounting also strengthens the effectiveness of financial management. Thus, it can be concluded that strategic financial management that is adaptable to technological developments is an important factor in driving sustainable business growth in medium-sized companies.